mRNA display with library of even-distribution reveals cellular interactors of influenza virus NS1 - Yushen Du; Judd F. Hultquist; Quan Zhou; Anders Olson; Yenwen Tseng; Tian-hao Zhang; Mengying Hong; Kejun Tang; Liubo Chen; Xiangzhi Meng; Michael J. McGregor; Lei Dai; et al. (Nature Communications, 2020)
Identification of low abundance proteins interacting with viral proteins can be challenging. Here, Du et al. develop an mRNA display approach with a library of even distribution, identify host proteins interacting with NS1 protein of influenza A virus, and show that one interactor provides a means to regulate cellular fatty acids synthesis.